Factors affecting internal audit effectiveness Jordanian public sector: Moderating effect of task complexity - Hamza Mohammad, Ahmad Alqudah (2020)
Internal Audit Effectiveness (IAE) is an indispensable element in helping public organisations to achieve their objectives through providing assurance and improving control effectiveness, risk management, and governance processes. Despite the extensive government’s efforts, the IAE within the Jordanian public institutions is relatively low, thus, it negatively affects the government objectives to combat corruption and to provide good services to public. Previous studies regarding the factors affecting IAE among public sector are limited and somewhat inconsistent. Therefore, the present study aimed to extend resourced-based and agency theories in the context of public sector, as well examining the moderating role of task complexity as a new construct to have a better understanding on the factors affecting IAE. This study hypothesized five factors affecting IAE, and five hypotheses on the moderating effects of task complexity on such relationships. Using the quantitative approach, this study distributed two sets of questionnaires among the financial managers and internal audit managers in Jordanian public institutions that are subject to the Audit Bureau Oversight. The returned questionnaires were 117 (41%). Results revealed the positive influence of top management support, internal auditors’ independence, internal-external auditors’ cooperation, and extrinsic rewards on IAE. Meanwhile, the internal audit department’s size had an insignificant influence on IAE. The findings also ascertained the considerable moderating effect of task complexity on the relationships between all studied factors on IAE except the extrinsic rewards factor, wherein task complexity has found to be insignificant on the relationship between extrinsic rewards and IAE. The findings suggest that the government should pay attention to the complex environment of public sector internal auditors' tasks, and they should overcome deficiencies in their internal resources to be effectively able to enhance the IAE.